Targeted Delivery of Celastrol by GA-Modified Liposomal Calcium Carbonate Nanoparticles to Enhance Antitumor Efficacy Against Breast Cancer - Wei Zhang; Jiping Li; Liling Yue; Chenfeng Ji (Pharmaceutics)
Background/Objectives: Breast cancer, a leading health threat affecting millions worldwide, requires effective therapeutic interventions. Celastrol (CEL), despite its antitumor potential, is limited by poor solubility and stability. This study aimed to enhance CEL’s efficacy by encapsulating it within glycyrrhizic acid (GA)-modified lipid calcium carbonate (LCC) nanoparticles for targeted breast cancer therapy. Methods: The 4T1 mouse breast cancer cells were used for the study. GA-LCC-CEL nanoparticles were prepared using a gas diffusion method and a thin-film dispersion method. GA-LCC-CEL were characterized using the zeta-potential, dynamic light scattering and transmission electron microscope (TEM). The in vitro release behavior of nanoparticles was assessed using the in vitro dialysis diffusion method. Cellular uptake was examined using flow cytometry and confocal microscopy. Intracellular ROS and Rhodamine 123 levels were observed under fluorescence microscopy. MTT and colony formation assays assessed cytotoxicity and proliferation, and apoptosis was analyzed by Annexin V-FITC/PI staining. Wound healing and transwell assays evaluated migration, and Western blotting confirmed protein expression changes related to apoptosis and migration. Results: GA-LCC-CEL nanoparticles displayed a well-defined core-shell structure with a uniform size distribution. They showed enhanced anti-proliferative and pro-apoptotic effects against 4T1 cells and significantly reduced breast cancer cell invasion and migration. Additionally, GA-LCC-CEL modulated epithelial-mesenchymal transition (EMT) protein expression, downregulating Snail and ZEB1, and upregulating E-cadherin. Conclusions: GA-LCC-CEL nanoparticles represent a promising targeted drug delivery approach for breast cancer, enhancing CEL’s antitumor efficacy and potentially inhibiting cancer progression by modulating EMT-related proteins.